On Janowski Starlike Functions - S. Owa (Journal of Inequalities and Applications, 2008)
For analytic functions f(z) in the open unit disc Ã°ÂÂ•ÂŒ with f(0)=0 and fÃ¢Â€Â²(0)=1, applying the fractional calculus for f(z), a new fractional operator DÃŽÂ»f(z) is introduced. Further, a new subclass Ã°ÂÂ’Â®ÃŽÂ»Ã¢ÂˆÂ—(A,B) consisting of f(z) associated with Janowski function is defined. The objective of the present paper is to discuss some interesting properties of the class Ã°ÂÂ’Â®ÃŽÂ»Ã¢ÂˆÂ—(A,B).